Small forest losses degrade stream macroinvertebrate assemblages in the eastern Brazilian Amazon - Brito, Janaina G. (2020)
Generally, habitat loss and fragmentation negatively affect biota, often in nonlinear ways. Such nonlinear responses suggest the existence of critical limits for habitat loss beyond which taxa experience substantial changes. Therefore, we identified change points for aquatic macroinvertebrate assemblages at both local-riparian and catchment extents in response to a forest-loss gradient in agriculture-altered landscapes of 51 small (1st to 3rd Strahler order) eastern Amazon streams. We used Threshold Indicator Taxa Analysis (TITAN) to identify change points for individual taxa and segmented regression analysis for assemblage richness. Considering the patterns of the cumulative frequency distributions of sum(Z−) maxima across bootstrap replications, peak changes in macroinvertebrate assemblages were at ∼9% (5–95 percentiles = 1–15%) of forest-loss at the catchment extent, and at ∼1.4% (5–95 percentiles = 0–35%) of forest-loss at the local-riparian extent. Although the assemblage change point at the site extent was less than that detected at the catchment extent, the markedly lower percentile range indicates that biotic assemblages are more clearly responsive to forest-loss at the catchment/network-riparian extents than the site extent. For catchment and site extents, segmented regression analysis determined a change point for assemblage richness at 57% and 79% of forest-loss, respectively. This indicates the low capacity of total richness to separate early and synchronous decreases of sensitive taxa from gradual increases of tolerant taxa. Our results also show that it is not enough to focus management and conservation actions on riparian zones, but that conservation strategies should be expanded to entire catchments as well. The sharp decline of sensitive taxa in response to removal of a small portion of forest cover, even at catchment extents, indicates that the Brazilian Forest Code is insufficient for protecting stream macroinvertebrates. Consequently, we recommend strategies to reverse the potential collapse of aquatic biodiversity, particularly through avoiding deforestation and forest degradation, encouraging socio-economic incentives for restoring degraded areas, creating protected areas, and maintaining the current protected areas. We argue that reducing habitat loss should be a top priority for conservation planners in tropical forests because the sensitivity of aquatic biodiversity to removal of riparian forest-cover in Amazon rainforests is higher than previously thought. Therefore, the Forest Code regulatory framework needs complementary regulation that may be achived by more restrictive State and biome policies. © 2019 Elsevier Ltd